Advances in Neural Computation, Machine Learning, and Cognitive Research Selected Papers from the XIX International Conference on Neuroinformatics, October 2-6, 2017, Moscow, Russia - Kryzhanovsky, Boris; Dunin-Barkowski, Witali; Redko, Vladimir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes new theories and applications of artificial neural networks, with a special focus on neural computation, cognitive science and machine learning. It discusses cutting-edge research at the intersection between different fields, from topics such as cognition and behavior, motivation and emotions, to neurocomputing, deep learning, classification and clustering. Further topics include signal processing methods, robotics and neurobionics, and computer vision alike. The book includes selected papers from the XIX International Conference on Neuroinformatics, held on October 2-6, 2017, in Moscow, Russia.
Keywords: Computational intelligence; Artificial intelligence; Biophysics; Computer simulation; Bioinformatics; Computational Intelligence; Artificial Intelligence; Biophysics; Computer Modelling; Computational and Systems Biology